Shear modulus G(0) and its correlations with matric suction, unconfined compression strength and tensile strength of an unsaturated residual soil - Motta, M. F. B.; Campos, T. M. P. de; Bernardes, G. P. [UNESP]; Viana da Fonseca, A.; Manzanal, D.; Sfriso, A. O. (Ios Press, 2015)
Several studies have been developed aiming to understand the behavior of saturated natural soils under small strains. A few studies have considered unsaturated soils, in most cases compacted soils and, eventually, disregarding the influence of suction in the analyses. Particularly in the case of unsaturated, natural residual soils, fairly few experimental data is available in the current literature regarding its behavior under small strains. In this context, this paper presents an experimental study to evaluate the influence of matric suction on the small-strain shear modulus G(0), unconfined compression strength and tensile strength of an undisturbed residual micaceous soil from Rio de Janeiro, Brazil. For this purpose, bender elements were employed to evaluate soil stiffness through the transmission of shear waves. The curve G(0) versus suction was related to the soil-water retention curve, determined by the filter paper and Haines' funnel techniques. Unconfined compression and Brazilian tests were carried out in order to obtain the relationship between unconfined compression strength and tensile strength and suction. The results show that, with the increase of matric suction the shear modulus initially increases, reaching a peak at a given suction, and then decreases continually. By comparing this curve with the soil-water retention curve, it is observed that the maximum soil stiffness corresponds to the second air-entry value of the double structured tested material. Furthermore, the effect of suction on the tensile strength shows the same trend: the maximum strength is attained at the second air-entry value. However, the unconfined compression strength behavior is different: there is a continuous increase in strength with increasing suction.
Keywords: Shear modulus; bender elements; matric suction; unconfined compression strength; tensile strength; residual soil